THE CORRELATION OF TOEFL TOWARD STUDENTS ENGLISH LANGUAGE DEVELOPMENT - Ermansyah Malik; Ana Rosida (UIN Alauddin Makassar, 2019)
This study explains the correlation between the TOEFL preparation course to the improvement of the ability to speak in English of the students at UniversitasFajar Makassar. The result of this study is expected to answer the phenomenon between the ability to score at the TOEFL test and the ability to speak of the students in the TOEFL preparation course. This study is also expected to be able to produce a TOEFL preparation class teaching method which is more suitable for improving students' speaking ability. This study uses a quantitative descriptive approach, using data in the form of numbers from each measurement instrument. This study analyzes data sets from two data collection instruments; TOEFL scores and Cambridge FCE speaking test scores, taken from the same group of study subjects. The data sets from both instruments are then compared to test the level of correlation. The data analysis and presentation are compiled based on statistical calculations using the correlation research analysis. The findings of this study indicate that the TOEFL score did not significantly correlate with the improvement in the speaking ability of the subjects. The results of the TOEFL training of study subjects with low / high scores did not show a significant increase in the ability to speak even though there was a linear relationship between the two pairs of the score. ABSTRAK Penelitian ini menjelaskan hubungan antara kursus persiapan TOEFL dengan peningkatan kemampuan berbicara dalam bahasa Inggris dari para siswa di Universitas Fajar Makassar. Hasil penelitian ini diharapkan dapat menjawab fenomena antara kemampuan untuk mendapatkan skor tinggi pada tes TOEFL dan kemampuan untuk berbicara siswa dalam kursus persiapan TOEFL. Penelitian ini juga diharapkan dapat menghasilkan metode pengajaran kelas persiapan TOEFL yang lebih mampu meningkatkan kemampuan berbicara siswa. Penelitian ini menggunakan pendekatan deskriptif kuantitatif, menggunakan data dalam bentuk angka dari masing-masing instrument pengukuran. Penelitian ini menganalisa kumpulan data dari dua instrument pengumpulan data; Skor TOEFL dan skor tes berbicara Cambridge FCE, diambil dari kelompok studi yang sama. Set data dari kedua instrument kemudian dibandingkan untuk menguji tingkat korelasinya. Analisis dan penyajian data disusun berdasarkan perhitungan statistic menggunakan analisis penelitian korelasional. Temuan penelitian ini menunjukkan bahwa kursus persiapan peningkatan skor TOEFL tidak berkorelasi signifikan dengan peningkatan kemampuan berbicara siswa didik. Hasil pelatihan TOEFL dari subyek penelitian dengan skor rendah/ tinggi tidak menunjukkan peningkatan yang signifikan dalam peningkatan kemampuan berbicara meskipun terdapat hubungan linier antara kedua variable pasang skor tersebut.Kata kunci: TOEFL, analisis statistik korelasi, koefisien korelasi